Tinjauan Pewarnaan Hemaktosilin-Eosin dan Periodic Acid-Schiff terhadap Kerusakan Hati Mencit yang Diinduksi Aloksan: A Review of Hematoxylin-Eosin and Periodic Acid Schiff Staining to Assess Alloxan-Induced Liver Injury in Mice - Putri, Nanik Aryani; Khristian, Erick; Durachim, Adang (Borneo Journal of Medical Laboratory Technology, 2023)
The liver is an organ that serves several functions in the body, including glucose metabolism to provide energy to other tissues. Hepatocytes are the primary functional cells of the liver, which also regulate liver glucose release via glucose transport protein-2. Hepatocyte injury could occur from toxic substances and diseases such as Diabetes Mellitus. Alloxan is an organic compound commonly used in diabetes research as a diabetogenic agent. Alloxan causes diabetes through selective inhibition of glucose-stimulated insulin secretion and induced formation of reactive oxygen species (ROS) that promotes pancreatic beta cell necrosis. Alloxan also affects the liver’s histological condition, including the hepatocellular structure and glycogen content. HE and PAS are used for evaluating this condition. However, both should be reviewed to evaluate their abilities. Mice were divided into control and test groups, each consisting of 5 mice. The test group was intervein-induced with 25, 50, and 100mg/KgBB alloxan on the second day of arrival. The mice’s livers were then taken on the seventh day; tissue processing was carried out to get 20 blocks of mice’s livers. Two 5-μm-thick paraffin-embedded sections from each group were stained with hematoxylin-eosin, and periodic acid Schiff, respectively. Mice’s liver slides are examined microscopically for the degree of injury and glycogen concentration for further evaluation using ImageJ digital imaging application. This study found that microscopical and ANOVA tests of both staining methods successfully produced significant differences between control and various dose alloxan-induced groups of mice.